The Mechanical Properties of Bismuth-based Ceramic Nanocomposite - Nurmalita, Nurmalita; Fikri, Ahmad; Masrullita, Masrullita; Sylvia, Novi; Fazira, Zetta; Jalaluddin, Jalaluddin; Ginting, Zainuddin (Malikussaleh University, Aceh, Indonesia, 2025)
This research investigated a Bismuth-based ceramic nanocomposite material with the stoichiometric composition Bi?.?Pb?.?Sr?Ca?Cu?O_y (abbreviated as B(P)SCCO-2223), synthesized via the solid-state reaction method. The fabrication process involved compound composition calculations and powder metallurgy using several high-purity oxide precursors, with bismuth oxide as the primary component. Heat treatment in the form of sintering was conducted at 846?°C for durations of 32 and 34 hours to examine its effects on the material’s physical properties. Scanning Electron Microscopy (SEM) analysis revealed layered grain structures with the presence of pores at grain boundaries. Energy Dispersive X-ray (EDX) analysis confirmed that the target 2:2:2:3 elemental ratio was achieved across all samples. X-ray Diffraction (XRD) analysis showed that the sample sintered for 34 hours exhibited the largest grain size of 48.07?nm. The holding time of 34 hours during the sintering process has provided sufficient opportunity for the crystal grains to grow larger. Scanning electron microscopy photos also show that longer sintering times make the empty space between the grains smaller because the crystal grains are closer together, followed by the pore size becoming smaller. This sample also demonstrated the highest oriented phase percentage (58.12%) and the lowest impurity level (6.05%). Mechanical properties, evaluated using Vickers microhardness testing, indicated that the 34-hour sintered sample had superior performance, with a Vickers hardness of 0.905?GPa, Young’s modulus of 74.2?GPa, yield strength of 0.301?GPa, fracture toughness of 5.17, surface energy of 0.18?J, and a brittleness index of 0.175. Overall, the study concluded that the physical properties of the ceramic nanocomposite improved with increased sintering duration.